Public Perceptions of Marine Plastic Litter: A Comparative Study Across European Countries and Seas - van Oosterhout, Lotte; Dijkstra, Hanna; van Beukering, Pieter; Rehdanz, Katrin; Khedr, Salma; Brouwer, Roy; Duijndam, Sem (Frontiers in Marine Science, 2022)
Marine plastic litter (MPL) is a growing global problem and its prevention requires public engagement and behavioral change. Statistics of public perceptions of MPL are scarce and hardly comparable due to varying definitions and interpretations of the concept. This study identifies and classifies relevant components of public perceptions of MPL based on a large-scale survey across 8 European countries sharing three European seas (North Sea, Baltic Sea, and the Mediterranean Sea). High levels of concern about MPL were observed throughout the EU and water pollution and plastics in oceans were consistently ranked in the top four most worrisome environmental challenges of our time. Most of the respondents (70%) reported noticing MPL, which influenced knowledge and feelings of responsibility with regards to MPL. The general public held companies and consumers most responsible for cleaning up MPL. Self-responsibility to reduce MPL varies considerably across and within countries, with the highest scores being reported in Greece and the lowest in the Netherlands. Public knowledge on the recyclability of plastics was low in all countries. At the marine region level, the lowest scores for concern, perceived consequences, and personal responsibility to reduce the use of plastics were reported in the North Sea region, followed by the Baltic Sea region, and the highest scores were recorded in the Mediterranean Sea region. Using these results, policy implications and possible intervention strategies are discussed, to improve and increase public awareness, understanding, engagement, and sense of responsibility to change lifestyles and purchasing behavior to prevent and reduce MPL, such as the design of multi-generational education programs to increase public awareness and understanding of the societal and environmental impacts of MPL.